Dysbiotic Fecal Microbiome in HIV-1 Infected Individuals in Ghana - Parbie, Prince Kofi; Mizutani, Taketoshi; Ishizaka, Aya; Kawana-Tachikawa, Ai; Runtuwene, Lucky Ronald; Seki, Sayuri; Abana, Christopher Zaab-Yen; Kushitor, Dennis; Bonney, Evelyn Yayra; Ofori, Sampson Badu; Uematsu, Satoshi; Imoto, Seiya; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
HIV-1 infected individuals under antiretroviral therapy can control viremia but often develop non-AIDS diseases such as cardiovascular and metabolic disorders. Gut microbiome dysbiosis has been indicated to be associated with progression of these diseases. Analyses of gut/fecal microbiome in individual regions are important for our understanding of pathogenesis in HIV-1 infections. However, data on gut/fecal microbiome has not yet been accumulated in West Africa. In the present study, we examined fecal microbiome compositions in HIV-1 infected adults in Ghana, where approximately two-thirds of infected adults are females. In a cross-sectional case-control study, age- and gender-matched HIV-1 infected adults (HIV+; n = 55) and seronegative controls (HIV-; n = 55) were enrolled. Alpha diversity of fecal microbiome in HIV+ was significantly reduced compared to HIV- and associated with CD4 counts. HIV+ showed reduction in varieties of bacteria including Faecalibacterium, the most abundant in seronegative controls, but enrichment of Proteobacteria. Ghanaian HIV+ exhibited enrichment of Dorea and Blautia; bacteria groups whose depletion has been reported in HIV-1 infected individuals in several other cohorts. Furthermore, HIV+ in our cohort exhibited a depletion of Prevotella, a genus whose enrichment has recently been shown in men having sex with men (MSM) regardless of HIV-1 status. The present study revealed the characteristics of dysbiotic fecal microbiome in HIV-1 infected adults in Ghana, a representative of West African populations.